Impact of Global Warming on soil microbial community - Kumar, Anil; Nisha, Nisha; Choudhary, Anil K; Suri, Vinod K (Indian Farming, 2017)
Various aspects of global warming pose greater influences on soil microbial community, their physiological activities, microbial biomass, growth, respiration rate, organic matter decomposition, etc. The elevated CO2 increasing temperature and soil moisture have direct influences on soil microbes, whereas conventional agricultural practices influence microbial communities indirectly through changes in soil management practices and vegetation cover. However, by altering soil environment through agricultural practices such as organic farming systems, addition of crop residues, biofertilizers, regulating soil moisture and temperature through mulches, the possible impact of climate change may be overcome to a greater extent.